2022
DOI: 10.1016/j.heliyon.2022.e08713
|View full text |Cite
|
Sign up to set email alerts
|

A novel epithelial-mesenchymal transition-related gene signature for prognosis prediction in patients with lung adenocarcinoma

Abstract: Traditional pathological diagnoses and clinical methods are insufficient to accurately predict the prognosis of lung adenocarcinoma (LUAD). Epithelial-mesenchymal transition (EMT) process is closely related to tumor cell migration. However, the prognostic value of EMT-related genes in LUAD is still unclear. In this study, we collected bulk RNA-sequencing (RNA-seq) and microarray data of LUAD patients from public databases and identified different expressed EMT-related genes in tumor and normal tissues. Then, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Transcriptomic-based signatures such as the 76GS [ 25 ] and KS [ 26 ] signatures and different scores based on canonical EMT markers have been developed to characterize score EMT [ 30 ] but in LUAD, most of them weakly associate with outcome. Recently, a novel EMT signature for prognosis prediction was published using public datasets and dbEMT 2.0 database [ 43 ]. In a previous work, we focused on EMT regulators and showed that decreased levels of miR-200a, b and miR-429 were significantly linked to DFS and OS in localized NSCLC [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptomic-based signatures such as the 76GS [ 25 ] and KS [ 26 ] signatures and different scores based on canonical EMT markers have been developed to characterize score EMT [ 30 ] but in LUAD, most of them weakly associate with outcome. Recently, a novel EMT signature for prognosis prediction was published using public datasets and dbEMT 2.0 database [ 43 ]. In a previous work, we focused on EMT regulators and showed that decreased levels of miR-200a, b and miR-429 were significantly linked to DFS and OS in localized NSCLC [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…More speci cally, EMT encourages tumor cells to separate from their original site and to move into the bloodstream, where they eventually colonize secondary organs (Qu et al 2023). Several studies have indicated that EMT-related genes (ERGs) can be used as markers for predicting the prognosis of LUAD patients (Cui et al 2022; (Feng et al 2022). Ferroptosis, a relatively recent discovery in the domain of programmed cell death, is distinguished by notable iron accumulation and lipid peroxidation in the course of the cell demise process, setting it apart from the mechanisms of apoptosis, necrosis, and autophagy (Li et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Non-small cell lung cancer (NSCLC) accounts for about 80–85% of primary lung cancers [ 2 ], with 70% of patients having progressed to intermediate or advanced/late stages by the time of diagnosis [ 3 ]. Lung adenocarcinoma (LUAD) accounts for approximately 40% of all newly diagnosed lung cancer cases and is the most common histologic form of NSCLC [ 4 , 5 ]. Despite significant advances in non-invasive surgery and immunotherapy in recent decades, 5-year overall survival (OS) rate is still as low as 17.4% [ 6 ].…”
Section: Introductionmentioning
confidence: 99%